Isolated Congenital Middle Ear Malformations: Comparison of Preoperative High-Resolution CT and Surgical Findings. (March 2020) - Zhang, Na; Li, Yi; Ma, Xiaobo; Wang, Danni; Li, Shuling; Yan, Fei; Zhao, Shouqin
Objectives: To compare preoperative temporal bone high-resolution computed tomography (HRCT) readings to intraoperative findings during exploratory tympanotomy for suspected cases of isolated congenital middle ear malformations (CMEMs) and summarize the malformations that can and cannot be diagnosed with HRCT. Methods: A retrospective study was conducted. All cases were confirmed as isolated CMEMs during surgery. Detailed clinical records were reviewed, with a focus on imaging and surgical findings. Results: One hundred and thirty-two patients and 145 ears were reviewed. Ninety cases (62.1%) could be identified as isolated CMEMs and at least one as middle ear anomaly using preoperative HRCT. Fifty-five cases (37.9%) were reported to be completely normal and the patients underwent exploratory tympanotomy to determine the final diagnosis. Stapes fixation, either alone or associated with other ossicular chain anomalies, contributed to 53.1% of the cases. Most cases of aplasia or dysplasia of the ossicular chain, for example, aplasia/dysplasia of the long process of the incus, aplasia of the stapes' superstructure, and atresia of the oval window were easily identified in preoperative HRCT. However, fixation of the ossicular chain can be elusive in HRCT, and exploratory tympanotomy is needed for a definitive diagnosis. Conclusions: HRCT provides helpful preoperative clinical information in CMEM and may obviate the need for middle ear exploration in some cases. The negative findings (anomalies that are difficult to identify through preoperative HRCT) and the positive findings (anomalies that are relatively easy to identify through preoperative HRCT) were summarized.